Shifts in Authenticity: Electronic Dance Music as Environment for Contemporary Folklore Forms - Gelažiūtė-Pranevičienė, Eglė (Tautosakos darbai, 2021)
The article discusses the most prominent creators of the Lithuanian post-folklore electronic music and their stylistic uniqueness, mainly focusing on the Electronic Dance Music (EDM) branch. An important fact is that the authors tend to create full-length music albums rather than single songs, thus emphasizing their conscious choice, constant and consistent activity. The two fields – modern and old – expand each other, attracting regular listeners with new expressions, thus continuing the development of folklore and enriching electronic music with cultural values and identity. Authentic folklore and its modernized forms do not overshadow each other and are often practiced in parallel. Electronic post-folklore music could be stylistically divided into EDM, ambient, and experimental subgenres. All of them often intertwine and shall be assigned to a genre depending on what prevails in the sound. Typically, folksongs are used in electronic dance music in two ways: by including an authentic sound recording or a folksong performance by contemporary singers. The second direction prevails, with the folklore content reaching the listener with a slightly altered timbre, depending on whether the singer is practicing authentic folklore or not. The stylistics of electronic music in each case reflects the author’s musical inclinations. The majority of the above-mentioned composers consistently work with at least one or more other musical styles, play more than one live instrument, often have their own recording studios. Due to its stylistic and structural agility, the only obligatory elements being the percussion and bass lines, electronic dance music can be very easily combined with basically any other material, in this case, folksong, without disrupting its integrity. The folksong is usually performed unchanged, maintaining its structure, melody, and text, with a minimum of “stretching” the rhythm, so that the song can be “loaded” into the aligned structure of the contemporary music. Harmony and the rhythm of EDM are essential factors (and thus variables) that point the direction and surprise the listener with new outcomes. Post-folklore dance music is expressed in various genres, combining folklore with dub, techno, house, trance, triphop, big-beat, and other styles, emphasizing the rhythmic and bass part, and improvising with the ethnic material. The works are usually based on consistent internal development, rather than on specific song forms typical of, for example, modern popular dance music, without overloading the pieces with sound layers, allowing each of them to unfold. Folksongs or their motifs appear as the main material, but instrumental folklore music or its recordings are not used – sometimes the whole of electronic music is supplemented with folk instruments while performing contemporary music part. Such music is especially welcome at festivals, intellectual music parties, listened to on digital music platforms, thus bringing the old culture closer to a modern human, creating conditions both for experiencing new expressions of folklore and becoming interested in authentic ethnic culture, returning to the roots, and learning the “pure” folklore.